2008
DOI: 10.1007/s10519-008-9230-3
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of Violence from Functional Aggression in Mice: An Ethological Approach

Abstract: The present study aims at delineating violence from aggression, using genetically selected high (SAL, TA, NC900) and low (LAL, TNA NC100) aggressive mouse strains. Unlike aggression, violence lacks intrinsic control, environmental constraints as well as functional endpoints. Conventional measures namely latency, frequency and duration were used initially to accomplish the objective of delineation using the above strains. However, these quantitative measures fail to reveal further details beyond the magnitude o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 69 publications
1
52
0
1
Order By: Relevance
“…Previous research on behavioral plasticity has revealed that animals with extreme personalities are less likely to exhibit plasticity while those whose personalities fall in the mid-range exhibit the most plasticity (West-Eberhard, 1989). For instance, among mice, the most aggressive individuals do not adjust their levels of aggression, whereas those who are less aggressive vary their aggression levels depending on the context (Natarajan, de Vries, Saaltink, De Boer, & Koolhaas, 2009). This tendency may explain the variation in personality ratings for these two lions.…”
Section: Rating Methodology and Behavioral Plasticitymentioning
confidence: 99%
“…Previous research on behavioral plasticity has revealed that animals with extreme personalities are less likely to exhibit plasticity while those whose personalities fall in the mid-range exhibit the most plasticity (West-Eberhard, 1989). For instance, among mice, the most aggressive individuals do not adjust their levels of aggression, whereas those who are less aggressive vary their aggression levels depending on the context (Natarajan, de Vries, Saaltink, De Boer, & Koolhaas, 2009). This tendency may explain the variation in personality ratings for these two lions.…”
Section: Rating Methodology and Behavioral Plasticitymentioning
confidence: 99%
“…Moreover, personality and plasticity are often correlated (e.g. passive mice adjust their levels of aggression according to social context but aggressive mice do not show context-dependent modulation of their behaviour; Natarajan et al, 2009; see Fig. S2C,D).…”
Section: Personality and Plasticitymentioning
confidence: 99%
“…A detailed description of these animals and their selection, the resident-intruder paradigm used for this study is available elsewhere [Natarajan et al, 2009]. The opponents used for this study was a docile strain Mas-Gro.…”
Section: Study Speciesmentioning
confidence: 99%
“…SAL mice also attack anesthetized opponents in neutral environments [Natarajan et al, 2009]. The SAL mice additionally attack their female cage-mates in particular after cage cleaning or after repeated inter-male interactions in the resident-intruder paradigm [Benus et al, 1990].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation